Integrated Optical Fiber Sensing System by Combing Large-Scale Distributed BOTDA/R and Localized FBGs. (31st December 2012) - Zhou, Zhi; He, Jianping; Ou, Jinping
Abstract : Structural health monitoring (SHM) has been regarded as a significant tool for the safety of civil infrastructures. Local fiber Bragg grating (FBG) sensor and distributed Brillouin optical fiber sensor have been successfully applied in civil engineering fields. Unfortunately, neither single FBG nor single Brillouin sensing technique can satisfy the requirements of simultaneously positioning full-scale structural damages and accurate local damage details. So it still matters to establish balance between localized high-precision measurement and large-scale distributed measurement with lower accuracy. This paper introduces an integration system by combining distributed Brillouin and local FBG sensors on one single-mode optical fiber. The temperature self-compensation and the data processing method of the integration system have been investigated. The integrated FBG/Brillouin sensor has been further packaged by glass fiber-reinforced polymer to be used as a robust and smart structural component. Finally the proposed integrated sensing system has been applied in three case studies, including investigation of reinforced concrete beam, smart cable, and smart steel strand to verify the feasibility. The test results illustrate that the integrated system can simultaneously provide accurate strain measurement at critical points by FBGs and the rough distributed strain measurement by Brillouin sensor, which can be further applied to various applications.